Palladium-Catalysed Construction of All-Carbon Quaternary Centres with Propargylic Electrophiles: Challenges in the Simultaneous Control of Regio-, Chemo- and Enantioselectivity - Kenny, Miles; Schröder, Sybrin P.; Taylor, Nicholas J.; Jackson, Paula; Kitson, Daniel J.; Franckevičius, Vilius (Synthesis, 2018)
This article describes the palladium-catalysed three-component coupling of 1,3-dicarbonyl compounds with nucleophiles and propargylic electrophiles for the generation of quaternary all-carbon centres in a single step, which necessitates the simultaneous control of regio-, chemo- and enantioselectivity. The use of propargyl enol carbonates, the source of two of the components, was found to be essential in maintaining high levels of regiocontrol and chemoselectivity, whereas a careful analysis of pKa trends of O-, C- and N-nucleophiles as the other coupling partner indicates that the highest levels of selectivity are likely to be obtained with relatively acidic species, such as phenols, 1,3-dicarbonyl compounds and aromatic N-heterocycles. Finally, studies towards the development of the catalytic enantioselective construction of quaternary all-carbon centres by means of alkenylation and allylic alkylation are disclosed.
Keywords: palladium; enantioselective catalysis; quaternary centres; propargylic electrophiles; 1,3-dicarbonyl compounds